Peroral endoscopic myotomy as first-line treatment in pediatric esophageal achalasia: a case report and literature review - Cuadros Mendoza, Carlos Augusto (2025)
Esophageal achalasia (EA) is a primary motility disorder characterized by the inability of the lower esophageal sphincter (LES) to relax properly. It is a rare condition in the pediatric population and therefore requires a high index of clinical suspicion. Delayed diagnosis can lead to significant morbidity. Treatment is aimed at reducing LES pressure, which helps relieve symptoms. We present the case of a 10-year-old male patient, with a history of IgE-mediated food allergy to dairy and peanuts, born and raised in the Turks and Caicos Islands, who was referred to our institution with a six-month history of progressive dysphagia for solids, postprandial vomiting, and significant weight loss. A barium esophagram revealed severe dilation of the esophageal body, with a distal esophagus showing the classic “bird’s beak” appearance. High-resolution esophageal manometry confirmed the diagnosis of type I EA. The patient underwent a peroral endoscopic myotomy (POEM), an innovative procedure that has proven to be effective, safe, and durable in the management of pediatric achalasia. This technique is available in experienced centers with specialized equipment and may represent a first-line treatment option in children with esophageal achalasia. To our knowledge, this is the youngest patient reported in Colombia with esophageal achalasia who achieved a successful clinical outcome following POEM.